Diseño y simulación de una antena fractal para detección de minas antipersonal artesanales de envase plástico - Blanco Gomez, Cristian Hernando (Escuela Colombiana de Ingeniería Julio Garavito, 2019)
As a consequence of the armed conflict in Colombia, a large part of the national territory is affected by the presence of Antipersonnel Mines (MAP). In Colombia, MAPs are manufactured mainly with unconventional materials such as plastic bottles, which makes their detection difficult. Initially, state-of-the-art research was carried out for: unconventional mine detection techniques, fractal antennas, wave propagation through material media. Subsequently, the design and simulation of the antenna was carried out, the characterization of the two media was carried out, their circuit models were built in distributed parameters, to simulate the physical phenomenon of the reflection of an electromagnetic signal, a principle used in radar technology of ground penetration (GPR). In the last stage, the results obtained were analyzed and it is evident that the designed antenna manages to generate a signal that, when reflected in the plastic mine, has enough power to be captured by a radar system, in this way it can be inferred that the fractal antenna if it can be used in mine detection.
Keywords: Antena fractal; Detección de minas; Minas antipersonal; Radar de penetración terrestre; Fractal antenna; Mine detection; Antipersonnel mines; Ground penetrating radar